How Does the Social Grouping of Animals in Nature Protect Against Sickness? A Perspective - Hart, Lynette A.; Hart, Benjamin L. (Frontiers in Behavioral Neuroscience, 2021)
Sickness behavior is broadly represented in vertebrates, usually in association with the fever response and acute infections. Currently the occurrence of sickness behavior in humans is quite variable, depending upon circumstances. In animals, the reactions to sickness behavior in a group member or potential group member evoke a specific response that reflects the species’ lifestyle. Groups of animals can employ varied strategies to reduce or address exposure to sickness. Most of these have scarcely been studied in nature from a disease perspective: 1) adjusting exposure to sick conspecifics or contaminated areas; 2) caring for an injured or sick group member; 3) peripheralization and agonistic behaviors to strange non-group conspecifics; and 4) using special strategies at parturition when healthy but vulnerable. Unexplored in this regard is infanticide, where newborn that are born with very little immunity until they receive antibody-rich colostrum, could be a target of maternal infanticide if they manifest signs of sickness and could be infectious to littermates and others. A major challenge and complication for such studies is that strategies used by species are likely to be highly specific and dependent upon the particular circumstances. What is needed is a more general awareness and consideration of the possibilities that avoiding or adapting to sickness behavior may be driving social behaviors of animals in nature.